2019
DOI: 10.1002/nau.24225
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electrical pain threshold assessment in the lower urinary tract

Abstract: Aims: Assessing the reliability of electrical pain threshold (PT) and evaluating the impact of stimulation frequency at different locations in the healthy lower urinary tract (LUT). Methods: Ninety subjects (age: 18.3-35.8 years, 40 females, 50 males) were randomly allocated to one stimulation site (bladder dome [BD], trigone, proximal, membranous (only males), or distal urethra). Using 0.5 Hz/1.1 Hz/ 1.6 Hz electrical stimulation (square wave, pulse width:1 ms), current perception thresholds (CPTs), PTs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Gender‐specific LUTESA results were shown by six studies, but only five of 80 studies (6.3%) statistically assessed the influence of gender on LUTESA. While these studies revealed conflicting results [22,26,27,74,75,77], the meta‐analyses of this review indicated no influence of gender on LUTCPTs.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Gender‐specific LUTESA results were shown by six studies, but only five of 80 studies (6.3%) statistically assessed the influence of gender on LUTESA. While these studies revealed conflicting results [22,26,27,74,75,77], the meta‐analyses of this review indicated no influence of gender on LUTCPTs.…”
Section: Resultsmentioning
confidence: 87%
“…Out of 80 studies, 61 exclusively applied CPTs [6,7,13–71], but four reported incomplete or no CPT results [14,32,61,64] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations